Meta-Analysis of the Impact of Reading Interventions for Students in the Primary Grades. Issue 2 (2nd April 2020) - Gersten, Russell; Haymond, Kelly; Newman-Gonchar, Rebecca; Dimino, Joseph; Jayanthi, Madhavi
Abstract: This meta-analysis systematically reviewed the most up-to-date literature to determine the effectiveness of reading interventions on measures of word and pseudoword reading, reading comprehension, and passage fluency, and to determine the role intervention and study variables play in moderating the impacts for students at risk for reading difficulties in Grades 1–3. We used random-effects meta-regression models with robust variance estimates to summarize overall effects and to explore potential moderator effects. Results from a total of 33 rigorous experimental and quasi-experimental studies conducted between 2002 and 2017 that met WWC evidence standards revealed a significant positive effect for reading interventions on reading outcomes, with a mean effect size of 0.39 (SE = .04, p < .001, 95% CI [0.32, 0.46]). Moderator analyses demonstrated that mean effects varied across outcome domains and areas of instruction.